Agarwood formation in Aquilaria beccariana and Aquilaria microcarpa in response to inoculation of newly isolated fungi from Brunei Darussalam - YUMNI HAZIQAH MOHAMMAD; Pooja Shivanand; Faizah Metali; Hussein Taha; NUR BAZILAH AFIFAH MATUSSIN; ABDUL MUIZZ AL-AZIM ABDUL-HALIM; ABDUL ZUL’ADLY MOHAIMIN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mohammad YH, Shivanand P, Metali F, Taha H, Matussin NBA, Abdul-Halim AMA, Mohaimin AZ. 2021. Agarwood formation in Aquilaria beccariana and Aquilaria microcarpa in response to inoculation of newly isolated fungi from Brunei Darussalam. Biodiversitas 22: 4131-4138. Aquilaria is an important agarwood-producing tree, but naturally occurring agarwood is rare. Artificial induction method is the most commonly used to produce agarwood in a short time. Out of the 21 species of Aquilaria, Brunei Darussalam houses two species that produce high quality agarwood, namely Aquilaria beccariana and A. microcarpa. The aims of this study are to artificially induce agarwood formation using eight different induction treatments: six fungal inoculant treatments with two control treatments, and to isolate and identify fungal strains from naturally infected agarwood tree using DNA barcoding. Agarwood formation was observed at four different time intervals i.e. 1, 3, 6 and 9 months of post-inoculation. Results exhibited that the area and the total length of discoloration zone were significantly greater at 6 and 9 months of incubation period. Induction treatment did not significantly affect the area and the total length of discoloration. FTIR analysis revealed that two aromatic compounds (C – H and C – C stretching) were detected at the wavelength ranges of 3000 – 2800 cm-1, and 1500 – 1400 cm-1 respectively, and OH group was detected at 3600 – 3400 cm-1.  Nine fungal strains from Aspergillus, Fusarium, Mucor and Trichosporon were isolated and identified from a naturally infected agarwood, and the last two fungi (Mucor and Trichosporon) were never been previously reported.